Foreign policy reports. - Foreign Policy Association, New York. (New York Foreign Policy Association, 1997)
Published twice a month except July and August.
Absorbed by its Foreign policy bulletin Sept. 1951.
Issues for Oct. 5, 1925-Jan. 29, 1926 called series 1925-26, no. 1-8.
Some vols. accompanied by supplements.
Title varies: Oct. 5, 1925-Jan. 29, 1926, Editorial information service.--Feb. 27, 1926-Mar. 4, 1931, Information service.
Keywords: World politics; International relations; United States -- Foreign relations